2000
DOI: 10.1093/pasj/52.3.421
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Region of the Seyfert 2 Galaxy NGC 3079

Abstract: We present a discussion on high-resolution studies of the nuclear region of NGC 3079 using observations of an H2O maser and continuum emission as well as H I absorption with a global VLBI network including the VLBA, the phased VLA and the Effelsberg 100 m telescope. Multi-frequency observations of the continuum emission reveal the spectra of continuum components and suggest a core-jet morphology. The H2O maser spots lie in a series of clusters distributed along a north-south direction, while we rule out any po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 0 publications
4
66
1
Order By: Relevance
“…The model proposed by Trotter et al (1998) differs significantly from that proposed by Sawada-Satoh et al (2000). According to these authors, the observed velocity drift of the maser feature at 1190 km s À1 is much larger than the velocity drift of the other maser features and is due to centripetal acceleration.…”
Section: Masermentioning
confidence: 76%
“…The model proposed by Trotter et al (1998) differs significantly from that proposed by Sawada-Satoh et al (2000). According to these authors, the observed velocity drift of the maser feature at 1190 km s À1 is much larger than the velocity drift of the other maser features and is due to centripetal acceleration.…”
Section: Masermentioning
confidence: 76%
“…This morphology, which is also seen in the X-rays (Fabbiano et al 1992;Dahlem et al 1998;Pietsch et al 1998) and in optical line emission (Ford et al 1986) has been interpreted as an outflow from a compact central engine that interacts with the dense gas in the nuclear environment (see discussion in Filippenko & Sargent 1992). The hypothesis that this outflow may be driven by accretion onto a supermassive black hole is reinforced by high-resolution VLA and global VLBI observations (e.g., Irwin & Seaquist 1988;Trotter et al 1998;Sawada-Satoh et al 2000) that reveal several aligned sources thought to be features of a nuclear jet.…”
Section: Ngc 3079mentioning
confidence: 85%
“…The weak extended emission that we observe Southeast of B, but which is not well constrained by our data, may be associated with components "A" and "C" as seen in the previous studies. Based on their spectra, the multi-component nature, and the position of the extended structure, Trotter et al (1998) and Sawada-Satoh et al (2000) argue that A and C can be identified with the fading and/or expanding components in a radio jet.…”
Section: Ngc 3079mentioning
confidence: 99%
“…( < ∼ 4.0 km s −1 yr −1 ; Nakai et al 1995;Baan & Haschick 1996;Trotter et al 1998;Satoh et al 1999;Sawada-Satoh et al 2000).…”
Section: Introductionmentioning
confidence: 99%